Building Awareness about the Dangers of Smoking and Its Impact on the Environment - Achmad, Musfirah; Mirza Togobu, Dian; Aliyah, St Nurul; Baharuddin, Baharuddin (Journal Pengabdian Masyarakat Politeknik Sandi Karsa, 2023)
Awareness about the dangers of cigarettes and their impact on the environment is an important aspect in efforts to maintain public health and nature preservation. Strong counseling and education is key in building this awareness. This community service aims to build public awareness about the dangers of cigarettes to human health and the environment and encourage positive actions to reduce their negative impacts. The methods used in community service include three stages, namely the planning stage, the implementation stage, and the evaluation stage. In conclusion, with joint commitment from various parties, we can build strong awareness about the dangers of cigarettes and encourage positive changes in people's behavior, both in terms of personal health and environmental conservation. First, robust and ongoing education about the dangers of cigarettes should be a key focus. By providing robust and relevant information, the public can understand the serious consequences of smoking and why it is important to avoid it. Then, a community-based approach involving families, schools, communities, and workplaces is important. Collaboration between stakeholders is needed to create a culture that does not support cigarette consumption